2008
DOI: 10.1007/s10734-008-9148-y
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management as a mechanism for technological and organizational change management in Israeli universities

Abstract: During the last decade, the higher education sector has experienced many pressures and changes (Hanna, Educause Review, 38(4), 25-34, 2003; Scott, Educause Review, 38, 64-80, 2003; Waterhouse, The power of e-learning: The essential guide for teaching in the digital age, 2005). Universities around the world are facing the need to adapt to a rapidly changing educational and social landscape, in which technology is both the main cause of change and a tool for dealing with the change. This study examines the orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 11 publications
0
28
0
2
Order By: Relevance
“…Corporations understand that by developing and investing in the knowledge based resources, they will go a long way towards ensuring the growth and future success of the organization. The competitive business environment will result in strategic planning tools for profit enhancement and product or service differentiation to meet the needs of the consumer [1].…”
Section: Discussion 31 Business Outlookmentioning
confidence: 99%
“…Corporations understand that by developing and investing in the knowledge based resources, they will go a long way towards ensuring the growth and future success of the organization. The competitive business environment will result in strategic planning tools for profit enhancement and product or service differentiation to meet the needs of the consumer [1].…”
Section: Discussion 31 Business Outlookmentioning
confidence: 99%
“…Universities around the world are facing the need to adapt to a rapidly changing educational and social landscape, in which technology is both the main cause of change and a tool for dealing with the change (Shoham & Perry, 2009). Management information systems are basically an integrated user machine system for input and output of data, processing of information and support for operations.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Information systems, in turn, can be understood as a group of interrelated components that collect, process, store and disseminate information to support decision making and managerial control (De Oliveira, de Vasconcelos, Queiroz, Queiroz, &Hékis, 2011). Shoham & Perry (2009) articulate that the role of technology in the organizations is complex and significant both as a creator of change and as a tool for dealing with change, sometimes simultaneously. The use of MIS allows for simpler processes, and as de Oliveira et al (2011) notes, institutions are resorting to technology to enhance and simplify information management.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Their study concluded that American higher education institutions as well as those in Asia, Europe, and Latin America have come to see knowledge management as central to their raison d'etre in today's know economy. Further, Shoham and Perry (2009) believe knowledge management to be critical to this process stating: "Knowledge management offers higher education an infrastructure for planning and managing innovation and change powered by cooperation, collaboration, and transmission of knowledge, as part of the organizations activity, while relying on and using information technology and supporting cooperation (p. 244)."…”
Section: Higher Educationmentioning
confidence: 99%